Base methods of measurements of parameters of quality of service in networks of data transmission - Курушкін, В. Є. (Problems of Informatization and Control, 2007)
The basic methods of measureitieMs ofeparameters of quality of service with use of the telecommunication equipment, in particular on an example of application of the equipment which realizes technology Frame Riley. It is shown, that loop the scheme of measurements the most suitable in procedures estimation qualities of service in networks of data transmission